Identification of the novel allele, HLA‐A*02:653, in an Italian patient. (21st September 2017) - Condello, R.; Picardi, A.; Battarra, M.; Troiano, M.; Andreani, M.
Abstract : HLA‐A*02:653 differs from A*02:01:01:01 by a C to T substitution in exon 2.